Blocking of Conducting Channels Widens Window for Ferroelectric Resistive Switching in Interface‐Engineered Hf0.5Zr0.5O2 Tunnel Devices. (11th June 2020) - Sulzbach, Milena Cervo; Estandía, Saúl; Gàzquez, Jaume; Sánchez, Florencio; Fina, Ignasi; Fontcuberta, Josep
Abstract: Films of Hf0.5 Z0.5 O2 (HZO) contain a network of grain boundaries. In (111) HZO epitaxial films on (001) SrTiO3, for instance, twinned orthorhombic (o‐HZO) ferroelectric crystallites coexist with grain boundaries between o‐HZO and a residual paraelectric monoclinic (m‐HZO) phase. These grain boundaries contribute to the resistive switching response in addition to the genuine ferroelectric polarization switching and have detrimental effects on device performance. Here, it is shown that, by using suitable nanometric capping layer deposited on HZO film, a radical improvement of the operation window of the tunnel device can be achieved. Crystalline SrTiO3 and amorphous AlO x are explored as capping layers. It is observed that these layers conformally coat the HZO surface and allow to increase the yield and homogeneity of ferroelectric junctions while strengthening endurance. Data show that the capping layers block ionic‐like transport channels across grain boundaries. It is suggested that they act as oxygen suppliers to the oxygen‐getters grain boundaries in HZO. In this scenario it could be envisaged that these and other oxides could also be explored and tested for fully compatible CMOS technologies. Abstract : The electroresistance on interface‐engineered hafnium‐oxide based ferroelectric tunnel junctions is analyzed. It is shown that capping the ferroelectric Hf0.5 Zr0.5 O2 (HZO) layer by ultrathin amorphous or crystalline dielectric layer, widens voltage‐operation regime, reduces device‐to‐device electroresistance variability, and enhances performance. Grain boundaries in the films and field‐induced conducting channels across are blocked by the capping layer.